Voting turnout, equality, liberty and representation: epistemic versus procedural democracy. Issue 3 (3rd May 2016) - Hill, Lisa
Abstract : Some epistemic approaches to democracy evince an exclusivistic approach to voting participation whereby high turnout elections are thought to produce adverse outcomes. On this view, high turnout introduces greater input from less politically competent citizens which, in turn, leads to bad governance. I challenge these claims from both an empirical and normative perspective by defending procedural democracy against epistemic democracy. I argue that it is mistaken to privilege epistemic considerations over other values that democracy is meant to serve, in this case, political equality, liberty and representativeness. Further, it is not clear that high voter turnout leads to worse government. In sum, (electoral) epistemic democracy is hard to justify given that (a) even in theory it is unconvincing as a form of democracy and (b) even on its own terms it is not demonstrably better than procedural democracy at 'performing' democracy.